IMPLEMENTASI PEMBLOKIRAN TELEPON DAN SMS PADA PERANGKAT BERBASIS ANDROID - Marlina Marlina (Jurnal Ilmiah Flash, 2015)
Nowadays, the usage of handphones is growing very quickly, so we can say that nearly everyone is now using the handphone. Handphone is used for voice telecommunication and for sending short message service (SMS), multimedia messaging service (MMS) and a lot of other smart aplications. In the other hand, as the usage of the handphones grow, there are a lot of unwanted telephone call and SMS. Therefore, we need an aplication to block the unwanted telephone call and SMS. This journal describe the implementation of a telephone and sms blocking application on the android based device.